Magnesium, magnesium alloys, and magnesium composites [ - Gupta, M. [ (Manoj)]; Nai, Mui Ling Sharon (John Wiley & Sons, 2011)
"Properties of Magnesium Composites for Material Scientists, Engineers and Selectors is the first book-length reference to provide an insight into current and future magnesium-based materials in terms of science,characteristics, and applications. It emphasizes the properties of magnesium-based composites and the effects of different types of reinforcements, from micron length to nanometer scale, on the properties of the resulting composites. With the popularity of magnesium-based materials in the automotive, aerospace, electronics, and sports equipment industries, and its unique role as a lightweight, energy-saving and high-performance material, both professionals and students will find this a must-haveresource"-- Provided by publisher